The Moderation Effect of Islamic Corporate Governance on Fraud Financial Statement Detection Using Fraud Hexagon - Ina Mutmainah; Dina Amalia Mahmudah (Universitas Negeri Malang, 2024)
Purpose: Given that Islamic corporate governance serves as a moderating variable, this study aims to examine the impact of the hexagon theory on fraudulent financial statements.Method: This study employed a quantitative methodology and garnered secondary data on Islamic commercial banks in Southeast Asia. Purposive sampling was carried out to collect data from 18 companies during five years (2017–2022), yielding 90 observations. The data analysis method employed Warp-PLS software version 8.0 and partial least square structural equation modeling (PLS-SEM).Findings: Study results demonstrate that financial stability significantly worsens the performance of fraudulent financial statements. Related party transactions, external auditors, director changes, C.E.O. education, company existence, and political connections did not affect governance, moderate the significant positive influence of financial stability, related party transactions, company existence, and political connections on fraudulent financial statements. Meanwhile, good oversight, external auditors, director changes, and C.E.O. education did not moderate the impact of misleading financial statements.Originality/Value: This research contributites significantly to the Islamic banking management. The Islamic corporate governance mechanism forms the process and structure of the entity’s supervisory, monitoring and advisory functions. The presentation of financial statements is carried out in an accountable and transparent manner based on Sharia principles, which can reduce the practice of financial statement fraud, so stakeholders will be more confident in investing.